(untitled) (Journal of Oriental Studies, 2016)
«the arab spring» as the phenomenon in the arab world, continues to develop. the tendency of distribution and deepening of similar events in the region which influence socio-political processes of neighboring countries was designated. in this flow changes syria is no exception. syrian conflict today defines relations between states in the region, is the Gordian knot that bound together the interests of many nations, the leading actors in international politics. the solution of the syrian problem is in focus of analysts and experts of the whole world. leading scientists of the Usa, europe, russia, the asian countries try to comprehend internal essence, driving forces, problems and prospects of the arab revolution, its role and a place in world history. Politicians of all ranks of the UN and the european Union unsuccessfully try to untangle the ball of contradictions connected with the syrian conflict and with consequences of arab spring.